The prevalence of hemoglobin Tacoma in Finland detected by HbA1c capillary electrophoresis. (1st February 2023) - Kangastupa, Päivikki; Åkerman, Kari; Risku, Sari; Väisänen, Matti; Kuusela, Rutta; Romppanen, Jarkko; Kouki, Annika; Sneck, Mia; Itkonen, Outi; Niemelä, Onni
Abstract: Previous studies have identified occasional cases of heterozygous Hb Tacoma in areas that have attracted Finnish immigrants, especially in Sweden and North America, but large studies of this slightly unstable beta variant in vitro have not been carried out. Here we determined the prevalence of hemoglobin variants across Finland. A total of 5059 samples from 11 different hospital districts were analyzed using HbA1c capillary electrophoresis and reviewed for atypical profiles (HbA1c, Capillarys 3 Tera, Sebia). 38 heterozygous Hb Tacoma cases were found (0.75%). The prevalence was highest in South Ostrobothnia (2.0%), located in western Finland, and second highest in the neighboring provinces (1.0–1.4%), but only two districts were devoid of variants. Heterozygous Hb Tacoma was confirmed by genetic testing (NM_000518.5(HBB):c.93G > T (p.Arg31Ser)). In addition, five other variants were found, suggestive of HbE, Hb Helsinki (two cases) and an alpha variant, as interpreted from the electropherograms. The fifth variant, belonging to the South Ostrobothnian cohort, remained unknown at the time of the initial analyses, but was later interpreted as homozygous Hb Tacoma and confirmed by hemoglobin fraction analysis (Hemoglobin(E), Capillarys 3 Tera). In a subsequent retrospective study of the electropherograms of routine HbA1c diagnostics, altogether nine homozygous Hb Tacoma cases were identified in South Ostrobothnia. While heterozygous Hb Tacoma is usually an incidental finding, it interferes with several HbA1c assays. The present study is the first demonstration of homozygous Hb Tacoma. The clinical presentations of homozygous Hb Tacoma are not known and need to be addressed in future studies.